Rediscovery of Pseudosinopla canaliculus (Reed, 1898) (Hemiptera: Heteroptera: Acanthosomatidae) with comments on its tribal classification and biogeography of South American Blaudusini - Carvajal, Mariom A.; Faúndez, Eduardo I.; Rider, David A. (Zootaxa, 2017)
Although the knowledge of South American Acanthosomatidae has increased in the past decade, still little is known about the features or natural history of several genera. Pseudosinopla canaliculus (Reed, 1898) is a rare Acanthosomatid, known so far only from its type. In this work, rediscovery of P. canaliculus in the regions Araucania and Los Rios in Chile is reported. Part of the internal female genitalia is described. The classification of Pseudosinopla within the Acanthosomatidae is analyzed resulting in the genus being transferred from the Lanopini to Blaudusini. Additionally, the biogeography and phylogenetic relationships of the group are discussed. It is hypothesized that Pseudosinopla forms part of a Gondwanian relict. And that similarly to other heteropterans, the association among several acanthosomatids with Nothofagus Blume forests has shaped the evolutionary patterns of the group. Finally, a nomenclatural note on the Blaudusinae is provided.